The maze runner - Dashner, James, 1972- (New York : Delacorte Press, 2009)
Sixteen-year-old Thomas wakes up with no memory in the middle of a maze and realizes he must work with the community in which he finds himself if he is to escape.
Keywords: Amnesia -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Labyrinths -- Juvenile fiction; Fantasy fiction; Science fiction